Building a prospective participatory approach for long-term agricultural sustainability in the Lezíria do Tejo region (Portugal) - ABRANTES, Patrícia; QUEIRÓS, Margarida; MOUSSELIN, Guilhem; RUAULT, Claire; ANGINOT, Étienne; FONTES, Inês (Cahiers de géographie du Québec, 2016)
Addressing the gaps between theory, research and practice, this paper explores a hybrid mindset of participatory action research (PAR), geoprospective and participatory geographical information system (PGIS). This approach brings together stakeholders, policy-makers and researchers – in an agricultural peri-urban region of Portugal, the Lezíria do Tejo region – to anticipate the possible changes in agricultural territories, while taking spatial dynamics into account. It uses a four-step methodology which integrates qualitative and quantitative approaches to select stakeholders’ interview areas, implement prospective workshops to engage and explore the stakeholders’ interests and encourage actions towards finding solutions for long-term agricultural sustainability in this region. The results from our study highlight that more participative approaches such as the ones developed here must be implemented towards decision-making, since they help to dispel the distrust between stakeholders, strengthen community cohesion and also contribute to build common solutions drawing upon various perspectives. From a PAR perspective, this work contributes to bridge the gap between academia and practitioners, as is shown by a willingness of the practitioners to actively participate in the research under progress.